2011
DOI: 10.1088/0957-4484/22/27/275603
|View full text |Cite
|
Sign up to set email alerts
|

A multi-scaled hybrid orthopedic implant: bone ECM-shaped Sr-HA nanofibers on the microporous walls of a macroporous titanium scaffold

Abstract: We report here, for the first time, a novel multi-scaled hybrid orthopedic implant material consisting of a macroporous Ti scaffold, whose macropores' walls have a microporous titania layer which is fully covered with nanofibers of Sr-doped hydroxyapatite (Sr-HA). The microporous titania layer is formed on and within the Ti scaffold by micro-arc oxidation, which firmly binds to the Ti substrate and contains Ca2+, Sr2+ and PO4(3-) ions. It is then hydrothermally treated to form Sr-HA nanofibers. During the hydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 50 publications
1
24
0
Order By: Relevance
“…The Ca2p peaks are located at 347.1 eV and 350.7 eV, and the P2p peak is located at 133.3 eV, which indicates that the Ca2p and P2p exists in the form of calcium phosphate phases (such as α-tricalcium phosphate, and amorphous calcium phosphate) in the detected surface layer 35 , which is a mixture of crystalline and amorphous structures 36 . The doublet peaks of Sr3d are located at around 132.7 eV and 134.5 eV, respectively, in accordance with those reported for SrTiO 3 37 . The Co2p peak is located at 780.3 eV, assigned to Co2p in CoTiO 3 38 .…”
Section: Resultssupporting
confidence: 89%
“…The Ca2p peaks are located at 347.1 eV and 350.7 eV, and the P2p peak is located at 133.3 eV, which indicates that the Ca2p and P2p exists in the form of calcium phosphate phases (such as α-tricalcium phosphate, and amorphous calcium phosphate) in the detected surface layer 35 , which is a mixture of crystalline and amorphous structures 36 . The doublet peaks of Sr3d are located at around 132.7 eV and 134.5 eV, respectively, in accordance with those reported for SrTiO 3 37 . The Co2p peak is located at 780.3 eV, assigned to Co2p in CoTiO 3 38 .…”
Section: Resultssupporting
confidence: 89%
“…To develop surface nanostructure, some other techniques are always employed, such as plasma spray, hydrothermal treatment (HT) and sol-gel method [11,22,23]. Among these techniques, the combination use of MAO and HT treatment (MAO-HT treatment) has received a lot of attention because it is able to produce a controllable surface hierarchical structure regardless the geometrical complexity of the titanium-based substrate [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…14,18,19,23 Studies on the chemical composition of nanotopographies have highlighted the significance of HA in promoting cell response, 29,30 and strontium-doped HA (Ca 10-x Sr x [PO 4 ] 6 [OH] 2 , Sr x -HA) with a Sr dose lower than 20% enhances osteoblast activity 31 and the positive effect of HA on bone integration. 32 In our previous works, we prepared nanogranulated HA, 33 Sr 0.5 -HA-, Sr 1 -HA-, Sr 2 -HA-, 32 and Sr 10 -HA- 34 patterned TiO 2 coatings using microarc oxidation (MAO), and also synthesized nanorod-shaped Sr 1 -HA-patterned TiO 2 coatings on macroporous titanium scaffolds 35 and dense titanium 36 using a two-step method of MAO and hydrothermal treatment (HT). It has been revealed that these multilayer coatings can firmly adhere to titanium substrates, 35 and the proliferation and differentiation of osteoblasts can be positively or negatively regulated by the narrow or wide interrod spacing of the Sr 1 -HA nanorods in the presence of serum, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…32 In our previous works, we prepared nanogranulated HA, 33 Sr 0.5 -HA-, Sr 1 -HA-, Sr 2 -HA-, 32 and Sr 10 -HA- 34 patterned TiO 2 coatings using microarc oxidation (MAO), and also synthesized nanorod-shaped Sr 1 -HA-patterned TiO 2 coatings on macroporous titanium scaffolds 35 and dense titanium 36 using a two-step method of MAO and hydrothermal treatment (HT). It has been revealed that these multilayer coatings can firmly adhere to titanium substrates, 35 and the proliferation and differentiation of osteoblasts can be positively or negatively regulated by the narrow or wide interrod spacing of the Sr 1 -HA nanorods in the presence of serum, respectively. 36 In the present study, the processes of osteoblast adhesion on the 3D Sr 1 -HA nanorod (with different interrod spacing) patterned coatings were investigated in serum-containing and serum-free cellculture media, together with 2D Sr 1 -HA nanogranule-patterned coating, to identify the effect of such nanotopographies on cell adhesion, especially the direct or indirect role of nanoscale surface cues in the regulation of cell adhesion.…”
Section: Introductionmentioning
confidence: 99%